Intellectual property rights, copynorm, and the fashion industry : a comparative analysis - Jankowska, Marlena (Routledge, 2023)
"This book traces the development of the fashion industry, providing insight into the business and, in particular, its interrelations with copyright law. The book explores how the greatest haute couture fashion designers also had a sense for business and that their attention to copyright was one of the weapons in protecting their market position. The work also confronts the peculiarities of the fashion industry as a means of demonstrating the importance of intellectual property protection while pointing out the many challenges involved. A central aim is to provide a copyrightability test for fashion goods based on detailed analysis of the legal regulations in the USA and EU countries, specifically Italy, France, the Netherlands, Germany and Poland. The book will be of interest to researchers and academics working in the areas of Intellectual Property Law, Copyright Law, Business Law, Fashion Law and Design"--